Green Economy – A New Dimension of Development - Raluca Mihalcioiu (EIRP Proceedings, 2013)
The “Green Economy” has been recognized by the international community (United Nations) as a key strategic tool for sustainable development. The transition to a green economy must be a task for all countries - for developing but also for developed countries. Economy and consumers should therefore be able to accelerate the economic transformation for their own interests. In developing this concept representatives of business, trade unions and environmental organizations are involved to ensure the practicability and application ways. After 4 years of crisis the concept of the green economy is an important principle if not to avoid but at least soften their negative effects. This paper focuses on definitions upon the concept of green economy and describes its characteristics in relation with the social market. It also tries to find the answer of the question if the green economy is the best way to choose in order to provide a sustainable economic development. Moreover, the article critically examines the concept of the green economy at the intersection between environment and economy.